A questionnaire based study to evaluate the perception, attitude and feedback of second year undergraduate students with respect to their pharmacology teaching methodology - Dutta, Sayeri; Devi, Ngangbam Kilabati; Das, Rajesh; Das, Ananya; Devi, N. Meena (International Journal of Research in Medical Sciences, 2017)
Background: Pharmacology, like any other branch of medicine, is progressing by leaps and bounds. Attempts have been made all over India to make the teaching of pharmacology more interesting and relevant. The course assessment instruments like feedback may help to know about the pros and cons of teaching and assessment methods. Currently, student’s feedback represents the primary means used by most programs to assess their methodology. Methods: A questionnaire was designed and given to second-year medical students to fill in and make suggestions according to the options given and were also free to express their own opinion at various places. Results: Majority of the students showed preference for tutorials, short answer questions and revision classes. About one third of the students felt that more group discussions should be introduced during teaching sessions. Students’ interest in microteaching and problem based learning was evident from their feedbacks. Conclusions: There is a need of conducting few microteaching sessions and more of clinical oriented problem based learning with MCQ based revisions at the end of each class in the pharmacology teaching at undergraduate level.